Corrosion Study of Mild Steel in Aqueous Sulfuric Acid Solution Using 4-Methyl-4H-1,2,4-Triazole-3-Thiol and 2-Mercaptonicotinic Acid—An Experimental and Theoretical Study - Mehmeti, Valbonë V.; Berisha, Avni R. (Frontiers in Chemistry, 2017)
The corrosion behavior of mild steel in 0.1M aqueous sulfuric acid medium has been studied using weight loss, potentiodynamic polarization measurements, quantum chemical calculations and molecular dynamic simulations in the presence and absence of 4-methyl-4H-1,2,4-triazole-3-thiol and 2-mercaptonicotinic acid. Potentiodynamic measurements indicate that these compounds mostly act as mixed inhibitors due to their adsorption on the mild steel surface. The goal of the study was to use theoretical calculations to better understand the inhibition. Monte Carlo simulation was used to calculate the adsorption behavior of the studied molecules onto Fe (1 1 1) and Fe2O3 (1 1 1) surface. The molecules were also studied with the density functional theory (DFT), using the B3LYP functional in order to determine the relationship between the molecular structure and the corrosion inhibition behavior. More accurate adsorption energies between the studied molecules and iron or iron oxide were calculated by using density functional theory with periodic boundary conditions. The calculated theoretical parameters gave important assistance into the understanding the corrosion inhibition mechanism expressed by the molecules and are in full agreement with the experimental results.